ANALYSIS OF THE EMOTIONAL CONCEPT OF PEUR / FEAR IN FRENCH AND UZBEK LANGUAGES - Davletov Kamaraddin Kurbonboevich, (EPRA International Journal of Research and Development (IJRD), 2022)
This article is devoted to the study of the methods and means of expression of the emotional concept of Peur / Fear in French and Uzbek, as well as its psychological, philosophical and social aspects. We have tried to classify these types of emotions, along with analyzing the place of fear in the system of human emotional experiences. In this article, we will try to describe the sequence in the process of analyzing the emotional concept of Peur / Fear. Since emotion is based on an emotional concept, we think it is expedient to study the place and psychological aspects of the place of fear in the system of human emotional experiences and to give it a general classification.